Papular xanthoma in a 6-month-old boy. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
A 14-month-old child in apparent good health, weighing 11 kg, came to our observation with a history of raised, yellowish, asymptomatic lesions appeared for the first time at the age of 6 months on the back and then gradually increased in number, while the previous lesions resolved spontaneously; the last lesion started at the age of 12 months on the forehead. The physical examination showed on the back a 12 x 7 mm, pink-yellowish nodule (Fig. 1), which became frankly yellow under the pressure of the fingers (Fig. 2). On the back there were also three pink-yellowish papules of about 3 mm in diameter and six pigmentary, sometimes anetodermic residua of variable diameter between 2 and 12 mm. On the right frontal region (Fig. 3) there was a skin-colored papule of 2 mm in diameter. There were no mucosal lesions. The laboratory tests, including cholesterol and triglycerides, were within normal limits. A biopsy was performed with a punch from a papule of the back and the histological examination (Fig. 4, 5) highlighted in the papillary dermis, immediately close to the epidermis, and in the high reticular dermis a monomorphic population of large cells with abundant foamy cytoplasm and central nucleus with evident nucleolus. There were a few histiocytes without Touton cells and inflammatory infiltrate. The diagnosis of papular xanthoma was done and its favorable prognosis with tendency to spontaneous resolution was confirmed to the family.